What are the real associations of homeostasis model assessment (HOMA) with body mass index and age - Horáková, Dagmar; Štěpánek, Ladislav; Štěpánek, Lubomír; Pastucha, Dalibor; Janoutová, Jana; Janout, Vladimír; Kron, Vladimír; Verner, Miroslav; Martiník, Daniel (Endokrynologia Polska, 2022)
INTRODUCTION: Insulin resistance (IR), a key pathogenesis mechanism of metabolic disorders, can be tested using homeostatic model assessment (HOMA). HOMA-IR quantifies peripheral tissue IR, whereas HOMA-β determines insulin secretion. The cross-sectional study aimed to examine non-linear associations of HOMA indices with age when adjusting for body mass index (BMI), and thus to investigate the indices' ability to reflect the real development of glucose metabolism disorders over time. MATERIAL AND METHODS: The sample comprised 3406 individuals without diabetes mellitus (DM) divided into those with normal glucose metabolism (NGT, n = 1947) and prediabetes (n = 1459) after undergoing biochemical analyses. Polynomial multiple multivariate regression was applied to objectify associations of HOMA with both age and BMI. RESULTS: Mean values of HOMA-IR and HOMA-β in individuals with NGT were 1.5 and 82.8, respectively, while in prediabetics they were 2.2 and 74.3, respectively. The regression proved an inverse non-linear dependence of pancreatic b dysfunction, expressed by HOMA-β, on age, but did not prove a dependence on age for HOMA-IR. Both indices were positively, statistically significantly related to BMI, with a unit increase in BMI representing an increase in HOMA-IR by 0.1 and in HOMA-β by 3.2. CONCLUSIONS: The mean values of HOMA indices showed that, compared with NGT, prediabetes is associated with more developed IR but lower insulin secretion. Both HOMA-IR and HOMA-b are predicted by BMI, but only HOMA-β is predicted by age. HOMA indices can reflect non-linear, closer-to-reality dependencies on age, which in many epidemiological studies are simplified to linear ones. The assessment of glucose metabolism using HOMA indices is beneficial for the primary prevention of IR and thus DM.
Keywords: homeostáza; Humans; lidé; Prediabetic State; Cross-Sectional Studies; Homeostasis; Insulin Resistance; Body Mass Index; glukosa; Glucose; prediabetes; index tělesné hmotnosti; průřezové studie; inzulinová rezistence